2016
DOI: 10.1209/0295-5075/116/50004
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a negative resistance in noisy coupled linear oscillators

Abstract: We report on the experimental observation of an emerging negative resistance in a system of coupled linear electronic RLC harmonic oscillators under the influence of multiplicative noise with long correlation time. When two oscillators are coupled by a noisy inductor, an analysis in the Fourier space of the electrical variables unveils the presence of an effective negative resistance, which acts as an energy transport facilitator. This might constitute a simple explanation of the now fashionable problem of ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Additionally, two independent and synchronized clocks are needed as well, one to define the initial conditions and the second to define the demanded dynamic changes. The solution is possible with the help of electronically synthesized circuits, using an analog computer built from different configurations of operational amplifiers [53][54][55] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, two independent and synchronized clocks are needed as well, one to define the initial conditions and the second to define the demanded dynamic changes. The solution is possible with the help of electronically synthesized circuits, using an analog computer built from different configurations of operational amplifiers [53][54][55] .…”
Section: Methodsmentioning
confidence: 99%
“…(See Methods, Circuit design and parameters, and refs. 53,54 for details.) Our experimental setup is designed so that the synthetic inductance and capacitance in each oscillator are L = 1 mH and C = 0.1mF, respectively, leading to natural frequency of each oscillator ω 0 /2π = 503 s −1 .…”
Section: Is a Real Diagonal Matrix And |ϕ〉mentioning
confidence: 99%
“…In recent years, electronic analogies have been successfully used to study key concepts and/or explore new focuses of complex quantum phenomena. In particular, they allowed for building experimental systems that offer certain implementation advantages-such as cost, complexity, and measuring protocols-over the original setups [51][52][53][54]. It is because of these features that electronic circuits have arisen as a powerful tool for exploring observables that obey the same mathematical description as those of the original quantum or classical systems.…”
Section: Dicke Model-lc Circuit Analogymentioning
confidence: 99%
“…The energies of the sites are arbitrarily chosen to be ω 1 =ω 2 =ω 3 =5 ps −1 , whereas the coupling between them are set to κ 12 =1 ps −1 , and κ 13 =κ 23 =0.5 ps −1 . Figure 1 shows some examples of platforms where single-excitation stochastic networks have been successfully implemented, namely optical tweezers [25], waveguide arrays [24], superconducting circuits [26][27][28], and electrical-circuit arrays [29]. Quite recently, it has been shown that stochastic quantum networks can also be implemented in fascinating platforms, such as nuclear magnetic resonance systems [30], and ion traps [31,32].…”
Section: Single-particle Dynamicsmentioning
confidence: 99%